Assessing the impact of magnesium-based nutritional education on lipid profiles in individuals with type 2 diabetes mellitus: a quasi-experimental study - Eram Albajri; Arwa S. Almasaudi; Hala H. Mosli; Noor A. Hakim; Reem O. Basaqr; Manal Naseeb (Diabetology & Metabolic Syndrome)
Abstract Background The potential therapeutic role of magnesium (Mg) in type 2 diabetes mellitus (T2DM) remains insufficiently studied despite its known involvement in critical processes like lipid metabolism and insulin sensitivity. This study examines the impact of Mg-focused nutritional education on lipid profile parameters, total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) in T2DM patients. Methods Thirty participants with T2DM were recruited for this within-subject experimental study. Participants underwent a three-month dietary intervention focused on increasing the intake of Mg-rich foods through nutritional education. Anthropometric measurements and lipids were assessed at baseline and after the intervention period, with the primary outcome variables including changes in lipid parameters. Results The findings showed a significant inverse association between dietary Mg intake and total cholesterol levels (r = − 0.36, p = 0.05). However, other parameters, TG, LDL-C, and HDL-C, were not found to be associated with Mg intake. Conclusion The study demonstrated an inverse association between Mg intake and cholesterol level. Providing nutritional education and guidance on incorporating Mg-rich foods into the diet may be a crucial strategy for improving the health and well-being of T2DM patients in Saudi Arabia. The feasibility and practicality of focused nutritional education as an intervention make it a low-cost, scalable, and sustainable approach that can be readily implemented in clinical and community settings. Further studies are needed to explore the long-term impact of dietary Mg interventions on a larger sample with longer education periods.